2016
DOI: 10.1002/star.201600219
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in corn flour applicability using lactic acid fermentation: A mechanistic study

Abstract: In order to enhance the applicability of corn flour using fermentation, Lactococcus lactis was isolated from pickle juice and was cultivated into a stable bacterial suspension with a bacterial concentration of 107–108 cfu/mL and a pH of 4.00. Combination of: (i) a fermentation liquid obtained by dilution of this bacterial culture with pure water to a final concentration of 20%; (ii) a temperature of 37°C; and (iii) a fermentation time of 4 days resulted in optimal fermentation of corn flour. The water‐retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The fermented dough has lower hardness, more cohesiveness, and chewiness as compared to the unfermented corn dough. Yang et al () studied the amylase‐rich fermented maize fortified flour and concluded better textured fermented flour which is in conformity with our study. Hardness is actually the maximum force applied on the dough, and lower hardness enables the easy processing of flour.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The fermented dough has lower hardness, more cohesiveness, and chewiness as compared to the unfermented corn dough. Yang et al () studied the amylase‐rich fermented maize fortified flour and concluded better textured fermented flour which is in conformity with our study. Hardness is actually the maximum force applied on the dough, and lower hardness enables the easy processing of flour.…”
Section: Resultssupporting
confidence: 92%
“…
Corn is considered to be the third most grown crop in the world, but most of the crop is transformed into fodder or ethyl alcohol and approximately only 5% is directly consumed by humans (Yang, Hui, Qiang, & Hua, 2017). The objective of modification is to enable the limited use of corn in the wide domain of applications.
…”
mentioning
confidence: 99%
“…It is reported that the acid-induced gelation due to LC and LF causes rigidity in flour and results in more hardness (Hu et al, 2007). Yang (Yang et al, 2017) worked on the fermented amylase-rich fortified maize flour and found better textured fermented flour concluded less hardness, more cohesiveness, gumminess, and chewiness which is in accordance to this study. Oladeji (Oladeji et al, 2014) analyzed and developed carrot-fortified fermented corn flour and concluded some favorable rheological attributes which is more compatible to produce a good product.…”
Section: Textural Analysis Of Corn Floursupporting
confidence: 88%
“…The changes in the DO and DD values of fermented rice starch were mainly due to alterations in the ordered structure of some starch molecules after fermentation. Fermentation modifies the chain distribution of branched starch, thereby reducing its short-range order [50,51]. Yang et al [51] obtained similar results in their experiments on lactic acid bacterial fermentation of corn starch, confirming the degradation of branched starch through fermentation.…”
Section: X-ray Diffractionmentioning
confidence: 75%